2019
DOI: 10.1016/j.urolonc.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The added value of systematic biopsy in men with suspicion of prostate cancer undergoing multiparametric MRI-targeted biopsy

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
6
24
0
Order By: Relevance
“…In our cohort, PI-RADS was correlated with a higher presence of PCa, csPCa, and a higher ISUP score. These findings were consistent with previous studies using either 1.5T 19 or 3T 20 .…”
Section: Conducting Mpmri Before Biopsy Significantly Improved the Pesupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, PI-RADS was correlated with a higher presence of PCa, csPCa, and a higher ISUP score. These findings were consistent with previous studies using either 1.5T 19 or 3T 20 .…”
Section: Conducting Mpmri Before Biopsy Significantly Improved the Pesupporting
confidence: 93%
“…Past studies have compared COG-TB and SB cores in a single cohort and reported that the combination of COG-TB and SB was superior to SB or COG-TB alone 18 . Several groups have also applied this to FUS-TB and found the combination of SB and FUS-TB to be superior, especially in the detection of csPCa [19][20][21] . In all studies except the PI-RADS score3 subgroup in Hansen et al 21 , TB alone showed a tendency to outperform SB alone.…”
Section: Conducting Mpmri Before Biopsy Significantly Improved the Pementioning
confidence: 99%
“…Recent studies showed that, in PIRADS score ≥3 men with SC on the combination of TB and SB, 5.5-27.7% of the SC were missed on TB. 4,[14][15][16] Our combination biopsy detected SC and GG ≥2 cancer in 191 and 183 men, respectively, whereas TB failed to detect SC and GG ≥2 cancer in 21 men for both (11.0% and 11.5%, respectively; data for GG ≥2 cancer is not shown), showing that the rate of our TB failure was within the range of the aforementioned data.…”
Section: Discussionsupporting
confidence: 69%
“…Follow-up data are presented in Table S6. None of the 62 men with a benign biopsy session had a GG ≥2 PCa at follow-up [median (interquartile range): 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)…”
Section: Follow-up and Mpmri Re-readingmentioning
confidence: 99%